Age-related impairment of cerebral blood flow response to KATP channel opener in Alzheimer's disease mice with presenilin-1 mutation. Issue 7 (July 2021) - Liu, Dong; Ahmet, Ismayil; Griess, Brandon; Tweedie, David; Greig, Nigel H; Mattson, Mark P
Local cerebral blood flow (CBF) responses to neuronal activity are essential for cognition and impaired CBF responses occur in Alzheimer's disease (AD). In this study, regional CBF (rCBF) responses to the KATP channel opener diazoxide were investigated in 3xTgAD, WT and mutant Presenilin 1(PS1M146V ) mice from three age groups using Laser-Doppler flowmetry. The rCBF response was reduced early in young 3xTgAD mice and almost absent in old 3xTgAD mice, up to 30%–40% reduction with altered CBF velocity and mean arterial pressure versus WT mice. The impaired rCBF response in 3xTgAD mice was associated with progression of AD pathology, characterized by deposition of intracellular and vascular amyloid-β (Aβ) oligomers, senile plaques and tau pathology. The nitric oxide synthase (NOS) inhibitor N ω -nitro-L-arginine abolished rCBF response to diazoxide suggesting NO was involved in the mediation of vasorelaxation. Levels of phosphor-eNOS (Ser1177) diminished in 3xTgAD brains with age, while the rCBF response to the NO donor sodium nitroprusside remained. In PS1M146V mice, the rCBF response to dizoxide reduced and high molecular weight Abeta oligomers were increased indicating PS1M146V contributed to the dysregulation of rCBF response in AD mice. Our study revealed an Aβ oligomer-associated compromise of cerebrovascular function in rCBF response to diazoxide in AD mice with PS1M146V mutation.